2023
DOI: 10.3390/w15101831
|View full text |Cite
|
Sign up to set email alerts
|

Fish Beta Diversity Patterns across Environmental Gradients in 63 European Shallow Lakes: Effects of Turbidity, Nutrient Enrichment, and Exotic Species

Abstract: The beta diversity among lakes is affected by natural environmental sorting, dispersal constraints, and anthropogenic disturbances. We hypothesized that fish beta diversity would increase towards lower latitudes and be higher in less disturbed lakes at within-region scale, but environmental disturbances could affect these patterns due to community homogenization or heterogenization (e.g., gain of exotic species) among lakes. We used generalized dissimilarity modeling to assess the relative importance of geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
1
0
0
Order By: Relevance
“…In fact, the latitude of study lakes and the monthly mean air temperature were strongly negatively correlated (Pearson's r = -0.97, p < 0.001). A previous study on various European lakes showed that environmental characteristics such as dimension, turbidity, nutrient enrichment, connectivity, and the presence of non-native sh can alter the rate of sh assemblage change over a latitude gradient (Menezes et al 2023). Our ndings demonstrate that the presence of invasive species is a driving force of the variation in community structure along a latitudinal gradient.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, the latitude of study lakes and the monthly mean air temperature were strongly negatively correlated (Pearson's r = -0.97, p < 0.001). A previous study on various European lakes showed that environmental characteristics such as dimension, turbidity, nutrient enrichment, connectivity, and the presence of non-native sh can alter the rate of sh assemblage change over a latitude gradient (Menezes et al 2023). Our ndings demonstrate that the presence of invasive species is a driving force of the variation in community structure along a latitudinal gradient.…”
Section: Discussionsupporting
confidence: 52%